Cancer Mortality in Hamburg (Germany) 1872-2019. - Stang, Andreas (Deutsches Ärzteblatt International, 2022)
Background: For a number of reasons, the cause-of-death statistics of the city of Hamburg are one of the most valid sources of data for the study of secular trends in cancer mortality in Germany. In this article, cancer mortality in Hamburg over the period 1872-2019 is presented. Methods: The sex-specific, raw, age-standardized (according to the world standard population), and age-specific cancer mortality rates for Hamburg, the German Empire, and the Federal Republic of Germany were determined from a variety of sources. The percentage of persons aged 60 and above in Hamburg was determined for the periods 1895-1950 and 1956-2019. Results: Raw cancer mortality rates rose in Hamburg from 1872 onward. After standardization for age, cancer mortality rates were nearly constant from 1905 to 1951. In contrast, age-standardized cancer mortality in Germany overall rose over the years 19051934, reaching the same level as Hamburg only in 1933. From 1951 onward, cancer mortality rose among men in Hamburg, reaching a maximum of 205 per 100 000 in 1967 and thereafter continually decreasing, down to a value of 120 per 100 000 in 2019. In women, cancer mortality was nearly constant from 1905 to 1958 and then fell continually until 2019 (85 per 100 000). The percentage of persons aged 60 or above was only 6% in 1895, 17% in 1950, and 23% in 2019. Conclusion: The high validity of cause-of-death statistics in Hamburg enabled an estimation of secular trends in cancer mortality. A steady decline in cancer mortality in all age groups and in both sexes was found in Hamburg, beginning in approximately 1990 at the latest.